ORBIT score: an useful predictor of small bowel rebleeding in patients under chronic anticoagulation - Gonçalves, Tiago Cúrdia (2018)
Background and study aims: Available scoring systems to assess the risk for major bleeding in patients on chronic anticoagulation seem inadequate in predicting higher diagnostic yields of small bowel capsule endoscopy (SBCE) or higher rebleeding rates in patients with suspected small bowel bleeding. The aim of this study was to evaluate the ability of the new ORBIT score in predicting positive findings of SBCE or higher rebleeding rates in chronically anticoagulated patients with suspected small bowel bleeding.Patients and methods: Retrospective analysis of 570 patients who consecutively underwent SBCE for the study of suspected small bowel bleeding. For each of the 67 patients who were on chronic anticoagulation, ORBIT score (Older age, Reduced hemoglobin/hematocrit, Bleeding history, Insufficient kidney function and Treatment with antiplatelets) was calculated. Patients were classified as high-risk (ORBIT score4) or low/intermediate-risk (ORBIT score<4). Data on SBCE findings, diagnostic yield and rebleeding were compared between groups.Results: When ORBIT score was calculated, 41 and 26 patients were classified as low/intermediate-risk and high-risk, respectively. When low/intermediate-risk and high-risk groups were compared, no differences were found in the diagnostic yield of SBCE (39.0% vs. 23.1%; p=.176). However, in high-risk patients, rebleeding was significantly more common than in low/intermediate-risk patients (80.0% vs. 36.6%; p=.003).Conclusions: In patients presenting with suspected small bowel bleeding and on chronic anticoagulation, the new ORBIT score seems promising in identifying those with a higher risk of rebleeding, in whom a closer follow-up and a more aggressive diagnostic and therapeutic strategy is advisable.